2011
DOI: 10.1007/s11136-011-9953-0
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic effects of fear of recurrence on the quality of life of cancer survivors and their caregivers

Abstract: Findings suggest that as expected, cancer severity was significantly related to individuals' FOR, which, in turn, played a key role in their mental health. Caregivers' FOR was also related to survivors' physical health, which suggests that programs aimed to manage FOR effectively should be provided not only to survivors but also caregivers, thereby improving the QOL of each person.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(118 citation statements)
references
References 48 publications
8
106
3
1
Order By: Relevance
“…Although advances in current treatments dramatically increase the number of cancer survivors in recent years, fear of recurrence is still a main concern for cancer patients (Kim et al, 2012). The findings of some studies conducted in Iran also indicated fear of recurrence as one of the major concerns among Iranian cancer patients (Taleghani et al, 2006;Abdollahzadeh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although advances in current treatments dramatically increase the number of cancer survivors in recent years, fear of recurrence is still a main concern for cancer patients (Kim et al, 2012). The findings of some studies conducted in Iran also indicated fear of recurrence as one of the major concerns among Iranian cancer patients (Taleghani et al, 2006;Abdollahzadeh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Studies also state that caregivers experience physical, social, psychological, and economical issues during the time they provide care to the patient; ultimately, causing an increase in care burdens and a deterioration in their quality of life (Morımoto, 2003). Studies report that characteristics such as age, gender, education level, income status, care period, changes in social life, and lack of family support have an effect on the quality of life of caregivers providing cancer patients with care (Tang et al, 2008;Özer et al, 2009;O'Hara et al, 2010;Alptekin et al, 2010;Kim, 2010;Tamayo et al, 2010;Collins, 2011;Hacıalioğlu et al, 2011;Kim et al, 2011;Song et al, 2011).…”
Section: Effects Of Care Burdens Of Caregivers Of Cancer Patients On mentioning
confidence: 99%
“…For example, both cancer survivors and their caregivers frequently report elevated stress and fear of cancer recurrence, which have been associated with poor mental and physical health outcomes, decreased quality of life [3], and reduced adherence to follow-up care [4]. Research has also documented the interdependence of mental and physical health within survivor-caregiver dyads [5][6][7] and shown that dyadfocused approaches to reducing breast cancer patients' depressive symptoms may be more efficacious than individual-oriented approaches [8]. Thus, there is increasing interest in developing dyad-focused research studies and interventions that involve both breast cancer survivors and their caregivers [9].…”
Section: Introductionmentioning
confidence: 99%